O acontecimento Ronaldo: a imagem pública de uma celebridade no contexto social contemporâneo - Paula Guimar?es Sim?es (2012)
The aim of this dissertation is to investigate the construction of the public image of soccer player Ronaldo Luís Nazário de Lima (Ronaldo). This examination is done by analyzing the individuation of key events of this celebritys life, so as to determine some of the values of contemporary society connected to his image. The overall concept of an event, which is the driving force of this analysis, is very significant not only for understanding certain moments of Ronaldos biography, but also for identifying this celebrity as a specific event himself. Derived from the discussion about the individuation of events, the method of analysis consists of three axes: 1) description; 2) narration; and 3) constitution of a pragmatic background. An analytic matrix of this sort creates a guide for comprehending five events that were remarkable in Ronaldos biography: 1) his retirement; 2) the Brazilian soccer teams defeat in the 1998 World Cup; 3) the 2002 World Cup championship; 4) his marriage to DaniellaCicarelli; and 5) his 2008 episode with the transvestites. This analysis leads to the identification of Ronaldo himself as a unique event. This thought is developed utilizing two dimensions: 1) Ronaldos power to affect society; and 2) the hermeneutic power of this celebrity-event. The originality of this dissertation is related specifically to the adoption of theconcept of an event when analyzing the public image of a celebrity.The analysis reveals that Ronaldos strong presence in the contemporary public scene is related to his charisma, specifically to the unique gifts of the body and spirit that he presents, thus creating an affective devotion to him from the public. These gifts are not derived exclusively from his technical skills as a soccer player. They also consist of socially sharedvalues, such as humbleness, determination, generosity, and solidarity. These and other values foster a positive hegemonic image of Ronaldo (although not a unanimous one) and help to explain the power this celebrity has to affect society. In addition, this analysis shows theoverall hermeneutic power of Ronaldo. In other words, the way his biography reveals features of contemporary social life. Individualism, sexism, hetero-normative behavior, shifting romantic relationships, and the entanglement of public and private lives are some importantaspects of contemporary society perceived in this analysis. These two dimensions the ability to affect society and Ronaldos hermeneutic power allows the interpretation of this celebrity as an event, thus validating the significance of this public character in the contemporary social context.